Net effect of wealth on health for COVID-19 – worldwide state comparison - Agata Żółtaszek; Alicja Olejnik (Rozwój Regionalny i Polityka Regionalna)
The wealth-health relationship is not unambiguous and constant. Indeed, a higher level of wealth affects individual and population health in two opposite ways. Increased risk factors raise the probability of some diseases. Conversely, better healthcare and awareness reduce the chances of developing these diseases or raise the likelihood of treatment and cure. Therefore, the overall impact on health or the “net effect” of wealth (positive or negative) may be challenging to determine. Moreover, this effect may not be fixed for different income groups. Thus, it states to reason that there may exist an “affluence point” changing the predominant impact of wealth (positive/negative), which we will refer to as the “health economic threshold”.